Malinowski and the Alps - Anthropological and Historical Perspectives - Burke, Patrick (bu,press, 2023)
Tucked away in the Italian Alps, in the town of Oberbozen-Soprabolzano lies the villa that the family of Bronislaw Malinowski and his first wife, Elsie Masson, called home from 1922 to 1935. Yet Malinowski himself never wrote about South Tyrol or the Alps in general. This volume features a series of essays that explicitly ponder Malinowski's intriguing influence on Alpine anthropology: Despite not having worked directly in or on the Alps, he nonetheless left anthropological traces through the works of others. The Malinowski Forum for Ethnography (MFEA) aims to uncover the ineffable presence in Alpine anthropology of Malinowski, a founder of modern social anthropology.